Efektifitas Penggunaan Reverse Osmosis Water dan Aquabidest dalam Meminimalkan Pertumbuhan Kuman di Humidifier pada Tindakan Terapi Oksigen - Muhammad Syamsul Arif S.N; Sarkum Sarkum; Rodhi Hartono (Jaringan Laboratorium Medis, 2019)
Oxygen is a basic human need that cannot be delayed. In patients who experience hypoxia management that must be done immediately is oxygen therapy. Oxygen tubes tend to be dry so they can cause irritation along the respiratory tract. Efforts to minimize these problems are by using a humidifier, but the use of a humidifier can be a place for bacterial growth. The study aimed to find out which is more effective more effective between the use of reverse osmosis water compared to the use of aquabidest in minimizing germ growth in the humidifier. This type of research is research (true experiment) with the design of posttest control group design. To find out the effectiveness of the two groups, the Mann-Whitney test was conducted. There was a significant difference between the bacteria colonies at the 8th, 16th and hourly observations, 24 in the aquabidest group with a p value of 0.018 and the Reverse osmosis water group with a p value of 0.007. There was no significant difference in bacterial colonies in the aquabidest group with Reverse Osmosis at the 8th, 16th and 24th hours observations with p values respectively 1.00, 1.00 and 0.74. There was no difference in effectiveness between the use of aquabidest compared to the use of Reverse Osmosis Water. Aquabidest and / or Reverse Osmosis Water can be used in a humidifier by using aquabidest and reverse osmosis water in a humidifier on oxygen therapy.